Overvalued Equity and Financing Decisions - Dong, Ming; Hirshleifer, David; Teoh, Siew Hong (Review of Financial Studies, 2012)
We test whether and how equity overvaluation affects corporate financing decisions using an ex ante misvaluation measure that filters firm scale and growth prospects from market price. We find that equity issuance and total financing increase with equity overvaluation; but only among overvalued stocks; and that equity issuance is more sensitive than debt issuance to misvaluation. Consistent with managers catering to maintain overvaluation and with investment scale economy effects, the sensitivity of equity issuance and total financing to misvaluation is stronger among firms with potential growth opportunities (low book-to-market, high R&D, or small size) and high share turnover.